The role of anticoagulation in venous thromboembolism primary prophylaxis in patients with malignancy: A systematic review and meta-analysis of randomized controlled trials. Issue 181 (September 2019) - Barbarawi, Mahmoud; Zayed, Yazan; Kheiri, Babikir; Gakhal, Inderdeep; Barbarawi, Owais; Bala, Areeg; Alabdouh, Ahmad; Abdalla, Ahmed; Rizk, Fatima; Bachuwa, Ghassan; Katato, Khalil
Abstract: Background: Venous thromboembolism (VTE) is a common cause of morbidity and mortality among patients with cancer. As such, we conducted a meta-analysis of randomized controlled trials (RCTs) that evaluated anticoagulants as primary prophylaxis against VTE in cancer patients. Methods: Pubmed/MEDLINE, Embase, and the Cochrane Library were screened for all RCTs that used anticoagulation therapy in cancer patients for primary prevention of VTE. The primary outcomes were VTE events. Secondary outcomes included all-cause mortality, VTE-related mortality and major bleeding. A random effects model was used to report the risk ratios (RR) with 95% confidence intervals (CIs), and odds ratios (ORs) with Bayesian 95% credible intervals for both direct and network meta-analyses, respectively. Results: Twenty-four RCTs were included totaling 13, 338 patients (7197 received anticoagulation and 6141 received placebo). The mean age ranged between 54.6 and 68.1 years, with 50.5% male. Compared with placebo, low-molecular-weight heparin (LMWH) or direct Xa inhibitors were associated with lower VTE events (RR 0.58; 95%CI 0.48–0.69, P < 0.001) and (RR 0.39; 95%CI 0.24–0.63, p < 0.001), respectively. LMWH was associated with decreased VTE and all-cause mortality when compared with placebo (P < 0.05). Regarding safety outcomes, LMWH and direct Xa inhibitors were not associated with increased risks of major bleeding (P > 0.05) when compared with placebo. Results regarding VTE events and major bleeding were consistent in both lung and pancreatic cancers. Conclusions: Both LMWH and direct Xa inhibitors were associated with a lower VTE events compared with placebo. However, this potentially protective effect must be balanced against the possible increased risk of bleeding for some patients. Highlights: Some LMWH seems to decrease both DVT and PE events and increase survival benefit. No overall survival benefit was noted for apixaban and rivaroxaban. Apixaban and rivaroxaban seem to decrease the composite VTE. Both LMWH and direct Xa inhibitors were associated with marginal bleeding risk. The remaining anticoagulants did not have any significant impact on VTE occurrence.